Analysing the priority interests of local communities with respect to mangrove forest ecosystem services in Indonesia - Supriyanto, Supriyanto; Maynawati, Aldila Fitri Radite Nur (Ecological Questions, 2026)
Mangrove forests provide a wide range of ecosystem services that directly and indirectly support the livelihoods of coastal communities. Understanding local perceptions and priority interests is critical to generate socially inclusive and ecologically effective conservation strategies. This study analysed the priority interests of local communities regarding mangrove ecosystem services in Indonesia, especially in North Sumatera (Sumut), North Kalimantan (Kaltara), and Southwest Papua (PBD). Data were collected using household surveys of 234 people and field observations. Descriptive statistics was selected to identify variations in priorities in three different regions. Results show that coastal protection was perceived as the most important ecosystem service of mangrove forests, while carbon storage was consistently considered the lowest priority. The main differences emerged in provisioning and supporting services in which Sumut and Kaltara expressed more concern in timber production than PBD. Yet PBD provided more attention in fisheries and nursery grounds, reflecting the different needs and ecological conditions in those regions. These findings underscore the importance of site-specific, participatory, and community-sensitive mangrove management. Conservation programmes should prioritise ecosystem services considered most important by communities, such as coastal protection, and strengthen understanding incentives for undervalued services, such as blue carbon. This will enable mangrove management policies to be more effective and accepted by local communities, contribute to ecological sustainability and coastal economic well-being, and support the effort of Indonesian government to mitigate greenhouse gas emissions through increased carbon sequestration nationwide.